(untitled) (Archaeologia Adriatica, 2022)
The paper deals with a fragment of a funerary mensa recovered in the archaeological excavations of the site of Galovac – Crkvina near Zadar. It is a rare example of this type of find in our region. Analogies can be found in funerary examples of northern Africa. It is associated with the Roman pagan burial, and possibly north African import from the 3rd – 4th centuries.